PRIBADI ROH KUDUS DALAM YOHANES 14:15-31 - Aryanto Budiono; GRACE ELISABETH MOONIK (JURNAL KADESI, 2023)
and spirit. Spirit in Hebrew "Ruakh" which means wind, breath of life and in Greek "pneuma" which means wind. The Holy Spirit is the person of God who works in the lives of believers who give life. This research is a literature review of Bible texts and Literature Study. Qualitative approach with text analysis using a theological perspective.